Evolutionary Psychology Meets Social Neuroscience - Morese, Rosalba; Auriemma, Vincenzo; Palermo, Sara (IntechOpen, 2022)
This book aims to open a debate full of theoretical and experimental contributions among the different disciplines in social research, psychology, neuroscience, and sociology and to give an innovative vision to the present research and future perspective on the topic. The fundamental research areas of evolutionary psychology can be divided into two broad categories: the basic cognitive processes, and the way they evolved within the species, and the adaptive social behaviors that derive from the theory of evolution: survival, parenting, family and kinship, interactions with nonparents, and cultural evolution. Evolutionary Psychology Meets Social Neuroscience explains at individual and group level the fundamental behaviors of social life, such as altruism, cooperation, competition, social exclusion, and social support.